2016
DOI: 10.7763/ijiet.2016.v6.764
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assisted Language Learning for Learning Arabic as a Second Language in Malaysia: Teacher Perceptions

Abstract: Abstract-A study was conducted on the perceptions of 35Malaysian school teachers on their use of Computer Assisted Language Learning (CALL) for teaching vocabulary to learners of Arabic as a Second or Foreign Language (ASL/AFL). Most teachers expressed their favour for using CALL, and especially recognized its potential in helping and encouraging such learners, but also pointed out its time consuming nature. CALL can assist in the teaching and learning of Arabic vocabulary, as it has also been useful in educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
(9 reference statements)
0
8
0
1
Order By: Relevance
“…Such as the study conducted by Maskor et al (2016) in which they indicated that major problem faced by Malay AFL learners lied about their lack of reading culture. In the same vein research conducted by Gharawi and Bidin (2016) stressed that the lack of practice was the core issue of the problems militating against learning of Arabic by Malay AFL learners. This was also confirmed by Omari (2016) who declared that the best environment for encouraging the use of foreign languages was unavailable in Malaysia.…”
Section: Discussionmentioning
confidence: 98%
“…Such as the study conducted by Maskor et al (2016) in which they indicated that major problem faced by Malay AFL learners lied about their lack of reading culture. In the same vein research conducted by Gharawi and Bidin (2016) stressed that the lack of practice was the core issue of the problems militating against learning of Arabic by Malay AFL learners. This was also confirmed by Omari (2016) who declared that the best environment for encouraging the use of foreign languages was unavailable in Malaysia.…”
Section: Discussionmentioning
confidence: 98%
“…The research study adopted a quantitative method of data analysis. The main rationale for this was that quantitative data concerning the online learning of the Arabic language using various forms of technologies would provide a clear view of student satisfaction and attitudes towards learning via remote education (Gharawi & Bidin, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Al Musawi et al (2016) disagrees with the previous discoveries by indicating that Arabic language teachers can utilize traditional and technology-based interventions to teach ASL. Gharawi and Bidin (2016) further argue that computer-assisted language teaching techniques facilitate students' ability to gain more experience.…”
Section: Issue/topic/themementioning
confidence: 99%
“…Moreover, Gharawi and Bidin (2016) and Batainah, Din, and Al Mashakbh (2018) scrutinized computeraided and hybrid ASL learning aspects and teaching and learning issues ASL, respectively. Likewise, O'Sullivan (2017), Zakaria, Atan, and Robe'ah-Yusuf (2019) and Jwaifell, Abu-Omar, and Al-Tarawneh (2018) focused on the professional development of trainer aspects of ASL pedagogy based on innovative and technology-based interventions while Carroll et al (2017), Shendy (2019), Alfaisal and Aljanada (2019) and Saiegh-Haddad and Ghawi-Dakwar (2017) technology integration or diffusion barriers.…”
Section: Synthesis Of Key Concepts and Theoretical Conceptsmentioning
confidence: 99%